2020
DOI: 10.1096/fj.201902815r
|View full text |Cite
|
Sign up to set email alerts
|

Small proline‐rich repeat 3 is a novel coordinator of PDGFRβ and integrin β1 crosstalk to augment proliferation and matrix synthesis by cardiac fibroblasts

Abstract: Nearly 6 million Americans suffer from heart failure. Increased fibrosis contributes to functional decline of the heart that leads to heart failure. Previously, we identified a mechanosensitive protein, small proline‐rich repeat 3 (SPRR3), in vascular smooth muscle cells of atheromas. In this study, we demonstrate SPRR3 expression in cardiac fibroblasts which is induced in activated fibroblasts following pressure‐induced heart failure. Sprr3 deletion in mice showed preserved cardiac function and reduced inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Multiple studies have shown the crucial roles of integrin and integrin-binding proteins such as Talin, Vinculin, Melusin, focal adhesion kinase (FAK) and integrin-linked kinase (ILK) in the pathogenesis of cardiac diseases through regulation of MAPKs [33,35,[37][38][39][40]. Consistent with our in vivo and in vitro findings, mice with deficiency of melusin, another muscle-specific integrin-binding protein, displayed a similar detrimental cardiac phenotype when challenged with PO.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies have shown the crucial roles of integrin and integrin-binding proteins such as Talin, Vinculin, Melusin, focal adhesion kinase (FAK) and integrin-linked kinase (ILK) in the pathogenesis of cardiac diseases through regulation of MAPKs [33,35,[37][38][39][40]. Consistent with our in vivo and in vitro findings, mice with deficiency of melusin, another muscle-specific integrin-binding protein, displayed a similar detrimental cardiac phenotype when challenged with PO.…”
Section: Discussionsupporting
confidence: 87%
“…A PCR array ( Supplemental Figure 13 ) demonstrated that Smad7 loss in fibroblasts is associated with markedly accentuated synthesis of mRNAs encoding structural matrix proteins (including Col1a1 , Col3a1 [collagen type III α1], Col5a1 [collagen type V α1], Col6a1 [collagen type VI α1], and Fn [fibronectin]; Figure 5, A–H ), basement membrane genes (including those encoding laminins and collagen IV chains; Supplemental Figure 14, A–G ), and matricellular proteins (including Postn , Tsp1 [thrombospondin 1], Tsp2 , Ccn2 [cellular communication network factor 2], and Vcan [versican]; Figure 5, A–H , and Supplemental Figure 14 ). Smad7 loss also accentuated fibroblast expression of Itgb1 ( Supplemental Figure 14I ), which encodes a TGF-β–inducible surface protein (integrin β1) with an important role in fibroblast activation ( 22 ) and proliferation ( 23 ). Moreover, Smad7 loss had profound effects on expression of genes associated with matrix remodeling, reducing Mmp1a levels and increasing expression of Mmp2 , Timp1 , Timp2 , and Adamts family members ( Supplemental Figure 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…ECM remodelling and altered cell–substrate interactions are crucial not only for cell anchorage, but also in regulating several cell functions [ 46 , 47 , 48 , 49 ]. To determine if collagen I impacts on cell behaviour, immunoblotting determined whole cell expression of proteins central to tubulointerstitial fibrosis in lysates from cells cultured on collagen I alone or following co-incubation with TGFβ1 (10 ng/mL) for 48 h. As expected, the pro-fibrotic cytokine increased expression of fibronectin to 314.8 ± 41.4% as compared to control, whilst minimal changes were observed in cells cultured on collagen I alone ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%